Material Flow Cost Accounting (MFCA) in Malaysia: an SME's case for cleaner production - Sulong, Farizah; Sulaiman, Maliah; Mohd Alwi, Norhayati (Technical University, Faculty of Business and Economics, 2013)
Material Flow Cost Accounting (MFCA) has the potential to address the profound impact that Small and Medium-Sized Enterprises (SMEs) in Malaysia may have on the natural environment. The main reason is that MFCA may attract the business community in Malaysia with its dual achievements of environmental and economic objectives simultaneously. The purpose of this paper is to highlight the facilitating factors and barriers experienced by one SME in Malaysia. The case study of an automotive SME showed that the main facilitating driver for the MFCA implementation was to reduce its financial burden, and not because of the increase in the level of environmental awareness. Despite that, the company was still able to achieve improved environmental performance through a reduction of its metal scrap (waste). In the Malaysian context, financial reasons driving environmental initiatives may be common among SMEs. Therefore one way to attract them to positively contribute to the natural environment is to encourage cleaner production using MFCA. The diffusion of innovations (DOI) theory was used to guide the study as it helped explain the factors that may influence the rate of MFCA implementation in the company. It was found that among the facilitating factors included MFCA’s own attribute of being compatible with the existing systems in the company. Further, the concept of MFCA was easily understood by employees in the various units. Other facilitating factors included the communication channels used, the MFCA team composition and also the extent of the change agents’ promotion efforts. Meanwhile the barriers included vendor constraints and the inability to link MFCA to the performance management system (PMS). Delayed supply of the new material by vendors had resulted in delayed cost savings, whereas acknowledgement of MFCA efforts in the PMS is needed to avoid future employee grievances. There are two pertinent contributions of the study. The facilitating factors and barriers of MFCA implementation in the case company may help other companies intending to adopt MFCA in future. Secondly,identifying a theoretical framework to explain the facilitating factors and barriers for MFCA implementation may enhance the “academic-practitioner” links.